Local religious norms, corporate social responsibility, and firm value - Zolotoy, Leon; O'Sullivan, Don; Chen, Yangyang (Journal of Banking & Finance, 2019)
We explore the impact of religious norms on the relationship between corporate social responsibility (CSR) and firm value. Employing a longitudinal sample of publicly listed U.S. firms, we document that strong local religious norms in the area surrounding firms’ headquarters attenuate the positive effect of CSR on firm value. In cross-sectional analyses, we find that the attenuating effect of strong local religious norms is amplified for firms with heightened litigation risk. We also find that the positive effect of CSR on firm value is amplified for firms headquartered in areas where prevailing religious norms are more tolerant of risk-taking. Further, we find that strong religious norms attenuated the positive association between CSR and abnormal stock returns during the 2008–2009 financial crisis. Taken together, our findings cast local religious norms as an important contextual factor that influences the insurance value of CSR—the protection that CSR affords against stakeholder reactions to negative events.